A statue of Jesus Christ standing in a wooden boat - Mumbai Archive Project Team (Jio Institute, 2024)
A statue of Jesus Christ standing in a wooden boat that is the kind Kolis use for fishing. Christian Kolis use this type of iconography to integrate their Christian faith with their primary source of livelihood.